Komunikasi silang budaya dalam penterjemahan bahasa Melayu: analisis budaya kebendaan (Jurnal Bahasa, 2022)
This article discusses about cross cultural communication in Malay translation. The writer discusses aspects of translation and communication, translation and culture, and translation in cross-cultural communication. Many people in this world try to bridge racial and cultural differences and to learn more from others. There is a tremendous need to strive to perceive issues through the culture's eve not dictated by skin tones, but with an open mind. The element of culture is divided into two: first, the material culture and second, the non-material culture. This article focuses on material culture based on English novels translated into Malay (Memoirs ofA Geisha, Harry Potter and The Sorcerers Stone, Harry Potter and the Chamber of Secrets, and Harry Potter and the Prisoner of Azkaban).